Iron-catalyzed chemoselective reduction of enimines to N-Allylic amines via hydrosilylation - Tewari, Tanuja; Shaikh, Maulali H.; Sharma, Himanshu; Vanka, Kumar; Chikkali, Samir H. (Asian Journal of Organic Chemistry, 2025)
Chemoselective hydrosilylation of unsaturated imines is challenging as the two double bonds compete for the reaction. Here in, we report an iron-catalyzed chemoselective hydrosilylation of enimines leading to the generation of allyl amines in the presence of phosphine ligand. A low-valent Fe(0) complex [(BDA)Fe(CO)3] catalyzed the hydrosilylation of enimine at room temperature and exhibited broad substrate scope including a variety of enimine (cinnamylimine, allylimine) and ketimine. Mechanistic investigations revealed that the reaction proceeds through an oxidative addition of the silane compound, leading to the formation of an iron hydride intermediate. Subsequently, a two-electron pathway facilitates the hydrosilylation of the enimine substrate. This has been supported by preparing a well-defined Fe(II)-silane complex and using it as a catalyst control. Based on experimental and computational investigations, a plausible Chalk-Harrod-type mechanism is proposed.
Keywords: Cinnamyl amine; Imine hydrosilylation; iron catalysis; Iron hydride; Phosphine